2002
DOI: 10.1530/rep.0.1240611
|View full text |Cite
|
Sign up to set email alerts
|

Sperm phospholipase Czeta from humans and cynomolgus monkeys triggers Ca2+ oscillations, activation and development of mouse oocytes

Abstract: ResearchFusion with a fertilizing spermatozoon induces the mammalian oocyte to undergo a remarkable series of oscillations in cytosolic Ca 2+ , leading to oocyte activation and development of the embryo. The exact molecular mechanism for generating Ca 2+ oscillations has not been established. A sperm-specific zeta isoform of phospholipase C (PLCζ) has been identified in mice. Mouse PLCζ triggers Ca 2+ oscillations in mouse oocytes and exhibits properties synonymous with the 'sperm factor' that has been propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
213
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(221 citation statements)
references
References 5 publications
7
213
0
1
Order By: Relevance
“…The latter hypothesis, on the other hand, proposes that after membrane fusion spermatozoa introduce a factor into the oocyte cytoplasm that has Ca 2+ -releasing ability. In recent studies, a novel sperm-specific isoform of PLC, named PLCζ, has been identified as the factor, and it has been reported that microinjection of complementary RNA for PLCζ from mouse, hamster, human and monkey spermatozoa elicits Ca 2+ oscillations in mouse oocytes equivalent to those seen during fertilization in mice [31,32]. Our results may support the sperm-factor hypothesis.…”
Section: Discussionsupporting
confidence: 82%
“…The latter hypothesis, on the other hand, proposes that after membrane fusion spermatozoa introduce a factor into the oocyte cytoplasm that has Ca 2+ -releasing ability. In recent studies, a novel sperm-specific isoform of PLC, named PLCζ, has been identified as the factor, and it has been reported that microinjection of complementary RNA for PLCζ from mouse, hamster, human and monkey spermatozoa elicits Ca 2+ oscillations in mouse oocytes equivalent to those seen during fertilization in mice [31,32]. Our results may support the sperm-factor hypothesis.…”
Section: Discussionsupporting
confidence: 82%
“…For example, while mammalian eggs express Fyn, Yes, and in some cases, Src (Talmor et al 1998, Talmor-Cohen et al 2004a), the results of two different studies indicate that these kinases are not required for the unique sperm-induced calcium oscillations (Kurokawa et al 2004a, Mehlmann & Jaffe 2005, which trigger egg activation in mammals (Carroll 2001). Instead, these calcium oscillations are triggered directly by a sperm-borne phospholipase that does not require PTK regulation (Cox et al 2002). The role of Src-family PTKs in later stages of mammalian fertilization has been addressed primarily using parthenogenetic activation.…”
Section: Introductionmentioning
confidence: 99%
“…tr-kit appears to activate the oocyte via a Fyn-phospholipase C␥1-mediated signaling pathway (13,14); a similar pathway has also been established in echinoderm and ascidian eggs (15). The discovery of the sperm-specific phospholipase C, on the other hand, offered the possibility that a phospholipase C protein of paternal origin was directly involved in triggering Ca 2ϩ oscillations during oocyte activation (16,17).…”
mentioning
confidence: 99%